Analisis Kebutuhan Media Board Game untuk Membiasakan Kemampuan Literasi Siswa Kelas III SD - Salma, Salma Annazhira; Usman, Herlina; Yunus, Mahmud (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
This research aims to analyze the need for the development of board game media as an innovative solution to optimize the literacy skills of third-grade elementary school students, which is driven by the low interest and literacy skills in Indonesian language learning. The low literacy skills are caused by a lack of student motivation and concentration, as well as less varied teaching methods, leading to boredom and a decrease in active student participation in the learning process. This research was conducted at SDN Rawamangun 12 using the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data collection was conducted through observation, in-depth interviews, and documentation studies involving third-grade homeroom teachers and students as research subjects. The needs analysis shows that to familiarize students with literacy skills, interactive learning media is needed to increase student engagement, and students are more interested in visual and game-based learning. Therefore, media packaged in the form of a board game can be an innovative solution to optimize students' literacy skills. Therefore, with this research, it is hoped that it can contribute to the development of creative learning media and optimize students' literacy skills.